Pedagogical Experiences: Emergent Conversations In/With Place/s (LEARNing Landscapes, 2021)
In this paper, we find and share emergent and relational learning practices through intra-actions with people, places, and materials. We are pedagogical and artistic practitioners who learn from experiencing the world with others and explore relational “intra-actions” (Barad, 2003) that facilitate knowledge-making practices. Contrary to mainstream Anthropocentric understandings, we do not see humans as the only agents in learning. Rather, we learn with other beings—places, materials, humans, and more-than-humans—as we attend to and move with each other.
Keywords: walking-with; knowledge emergence; making; relationality; pedagogy